2021
DOI: 10.1596/1813-9450-9576
|View full text |Cite
|
Sign up to set email alerts
|

How Do Digital Technologies Affect Household Welfare in Developing Countries? Evidence from Senegal

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Bahia et al, (2020) found that mobile broadband internet boosted household consumption and contributed to a reduction in moderate and extreme poverty in Nigeria. In Senegal, a World Bank report on the impact of digital technologies on household welfare (Rodriguez-Castelan et al, 2021) confirmed this result. Hjort & Poulsen (2019) also found that broadband internet enabled more rapid job creation and economic activity in 12 sub-Saharan countries.…”
Section: * * *mentioning
confidence: 76%
“…Bahia et al, (2020) found that mobile broadband internet boosted household consumption and contributed to a reduction in moderate and extreme poverty in Nigeria. In Senegal, a World Bank report on the impact of digital technologies on household welfare (Rodriguez-Castelan et al, 2021) confirmed this result. Hjort & Poulsen (2019) also found that broadband internet enabled more rapid job creation and economic activity in 12 sub-Saharan countries.…”
Section: * * *mentioning
confidence: 76%
“…Bahia et al, (2020) found that mobile broadband internet boosted household consumption and contributed to a reduction in moderate and extreme poverty in Nigeria. In Senegal, a World Bank report on the impact of digital technologies on household welfare (Rodriguez-Castelan et al, 2021) confirmed this result. Hjort & Poulsen (2019) also found that broadband internet enabled more rapid job creation and economic activity in 12 sub-Saharan countries.…”
Section: * * *mentioning
confidence: 76%
“…Bahia et al, (2020) found that mobile broadband internet boosted household consumption and contributed to a reduction in moderate and extreme poverty in Nigeria. In Senegal, a World Bank report on the impact of digital technologies on household welfare (Rodriguez-Castelan et al, 2021) confirmed this result. Hjort & Poulsen (2019) also found that broadband internet enabled more rapid job creation and economic activity in 12 sub-Saharan countries.…”
Section: * * *mentioning
confidence: 76%